2015
DOI: 10.1108/nfs-03-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential and quality characteristics of functional mutton patties incorporated with cabbage powder

Abstract: Purpose – The purpose of this paper is to investigate the efficacy of cabbage powder as a source of natural antioxidants and dietary fibre for the development of functional mutton patties. Antioxidants are the first line of defence against the oxidative damage to body’s macromolecules resulting in pathogenesis of various diseases including cancers and cardiovascular diseases. The supply of antioxidants from vegetative sources along with different meat products may serve as an excellent alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
17
28
1
Order By: Relevance
“…The coliforms went undetected in any of the goat meat sausages enclosed with or without edible films, indicating the absence of coliforms due to their destruction during cooking at 140°C. The results agreed with the findings of several studies involving processing of the meat products at such a high temperature (Jamwal, Kumar, Bhat, Kumar, & Kaur, ; Malav, Sharma, Kumar, & Talukder, ; Singh, Kumar, Bhat, & Kumar, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The coliforms went undetected in any of the goat meat sausages enclosed with or without edible films, indicating the absence of coliforms due to their destruction during cooking at 140°C. The results agreed with the findings of several studies involving processing of the meat products at such a high temperature (Jamwal, Kumar, Bhat, Kumar, & Kaur, ; Malav, Sharma, Kumar, & Talukder, ; Singh, Kumar, Bhat, & Kumar, ).…”
Section: Resultssupporting
confidence: 90%
“…agreed with the findings of several studies involving processing of the meat products at such a high temperature (Jamwal, Kumar, Bhat, Kumar, & Kaur, 2015;Malav, Sharma, Kumar, & Talukder, 2015;Singh, Kumar, Bhat, & Kumar, 2015).…”
Section: Coliform Count (Log Cfu/g)supporting
confidence: 91%
“…After cooking, the percent increase in potassium was 7% whilst, percent decrease in rest of the minerals was observed as sodium 21, calcium 2, magnesium 2, iron 1, manganese 11, copper 3 and zinc 5 (Kawashima and Soares, 2003). Recently, Malav et al (2015) reported calcium content in cabbage up to 45 mg/100g F.W. that was higher than the current study result.…”
Section: Discussioncontrasting
confidence: 72%
“…() also indicated that there was a positive relationship between TPC and antioxidant capacity. The increased antioxidant activity of meat products by addition of plant materials has been recognised in other research, such as addition of cabbage powder into mutton patties (Malav et al ., ) and guava powder into sheep meat nuggets (Verma et al ., ), mainly due to the phenolic compounds and antioxidant activity of these plant powders.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant activity of the sausage samples was analysed by radical scavenging activity using 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH), according to the method by Malav et al . (). Four grams of chicken sausage samples were mixed with 20 mL of methanol in a 50‐mL test tube.…”
Section: Methodsmentioning
confidence: 97%